Supplier Selection and Evaluation by Fuzzy-AHP Extent Analysis: A Case Study RMG Sector of Bangladesh - Mohammad M Rahman; Kazi B Ahsan (International Journal of Engineering and Management Research, 2019)
The ready-made garments (RMG)is a rapid growing industry in Bangladesh and contributing significantly in the country’s economy. Effective supplier selection policy has significant strategic importance in the performance of such fast moving consumer goods industry. The supplier selection process is essentially a multi-criterion decision making problem which, therefore, must be developed systematically. Many models have been developed and proposed to find optimum solutions of this complex decision-making problem. Fuzzy Analytic Hierarchy Process (Fuzzy-AHP), which is a derived extension of classical Analytical Hierarchy Process (AHP),is an excellent method for deciding among the complex structure at different levels. In this paper an extent analysis of Fuzzy-AHP has been applied to evaluate and select the best supplier agency providing most satisfaction. The evaluation criteria are developed particularly for an RMG manufacturer in Bangladesh context and used successfully in the proposed model. A detailed implementation process is presented in this paper and finally the best supplier agency has been proposed from the outcome of the model.